Pulmonary Anthracosis in A Lion Tailed Macaque (Macaca silenus), An Endangered Primate Species - A Case Report - Ibrahim, Anees; Alexander, Jacob; S S, Devi (Jurnal Medik Veteriner, 2023)
Anthracosis is the blackish pigmentation of the lung parenchyma and tracheobronchial tree. A female Lion Tailed Macaque aged 19 years was being kept captive in Thiruvananthapuram Zoo for 17 years. On 30th November 2019, the animal was found dead in the zoo and was subjected to a necropsy at the zoo hospital. The necropsy revealed diffused black deposits throughout the lungs on gross examination. On histopathological analysis, blackish deposits could be found throughout the lung parenchyma as free particles in addition to those observed in macrophages. Vehicular emissions seem to have caused the condition to develop. This is the first reported case of anthracosis in a Lion Tailed Macaque. The condition can adversely affect the health and life expectancy of Lion Tailed Macaques. The conservation status of Lion Tailed Macaques makes it important to prevent such pathologies from affecting the relatively smaller population of the species.